PENGARUH PERENCANAAN KEBUTUHAN BAHAN BAKU DAN PENGAWASAN MUTU BAHAN BAKU TERHADAP KELANCARAN PROSES PRODUKSI PADA INDUSTRI OTOMOTIF - Ari Soeti Yani (Universitas Bunda Mulia, 2017)
The purpose of this study is to determine the effect of raw material requirements planning and the empirical study of raw materials quality control towards the success of production process at PT. Inkoasku in North Jakarta. The company has been established since 1974 or had been around for 40 years. The sample that will be studied in this paper is derived from the monthly report data from PT. Inkoasku in North Jakarta from the period of January 2013 to December 2015. This study analyzes the relationship between effect of raw material requirements planning and the empirical study of raw materials quality control towards production process at PT. Inkoasku in North Jakarta. Statistic method used in this study is the multiple linear regression to first test the classical assumption. The results indicate that the raw material requirements planning has a partially positive influence towards the smoothness of the production process at PT. Inkoasku in North Jakarta. The raw materials quality control has a partially negative influence towards the smoothness of production process at PT. Inkoasku in North Jakarta. Keywords: Raw Materials Requirement Planning, Raw Materials Quality Control, Production Process.